Relational engagements of the indigenous Americas : alterity, ontology and shifting paradigms - Baltus, Melissa R.; Baires, Sarah E., 1985- (Lexington Books, 2017)
"Dynamic Worlds, Shifting Paradigms critically examines our current understanding of relational theory and the ontological turn in archaeological studies of the pre-contact Americas."--Provided by publisher.